Charge storage mechanism of activated manganese oxide composites for pseudocapacitors1. Issue 24 (28th June 2015) - Wu, Tzu-Ho; Hesp, David; Dhanak, Vin; Collins, Christopher; Braga, Filipe; Hardwick, Laurence J.; Hu, Chi-Chang
<x xml:space="preserve">Abstract</x> Manganese oxides can undergo an electrochemical activation step that leads to greater capacitances, of which the structural change and mechanism remains poorly understood.